Dietary choline intake and health outcomes in U.S. adults: exploring the impact on cardiovascular disease, cancer prevalence, and all-cause mortality - Peng Jieru; Shanshan Zhang; Lin Cai; Wencheng Long; Yueshan Wang; Lu Zhang; Yao Dong; Wenqi Zhang; Juan Liao; Chunxia Yang (Journal of Health, Population and Nutrition, 2024)
Abstract Background Choline, an indispensable nutrient, plays a pivotal role in various physiological processes. The available evidence regarding the nexus between dietary choline intake and health outcomes, encompassing cardiovascular disease (CVD), cancer, and all-cause mortality, is limited and inconclusive. This study aimed to comprehensively explore the relationship between dietary choline intake and the aforementioned health outcomes in adults aged > 20 years in the U.S. Methods This study utilized data from the National Health and Nutrition Examination Survey between 2011 and 2018. Dietary choline intake was evaluated using two 24-h dietary recall interviews. CVD and cancer status were determined through a combination of standardized medical status questionnaires and self-reported physician diagnoses. Mortality data were gathered from publicly available longitudinal Medicare and mortality records. The study utilized survey-weighted logistic and Cox regression analyses to explore the associations between choline consumption and health outcomes. Restricted cubic spline (RCS) analysis was used for dose‒response estimation and for testing for nonlinear associations. Results In our study of 14,289 participants (mean age 48.08 years, 47.71% male), compared with those in the lowest quintile (Q1), the adjusted odds ratios (ORs) of CVD risk in the fourth (Q4) and fifth (Q5) quintiles of choline intake were 0.70 (95% CI 0.52, 0.95) and 0.65 (95% CI 0.47, 0.90), respectively (p for trend = 0.017). Each 100 mg increase in choline intake was associated with a 9% reduced risk of CVD. RCS analysis revealed a linear correlation between choline intake and CVD risk. Moderate choline intake (Q3) was associated with a reduced risk of mortality, with an HR of 0.75 (95% CI 0.60–0.94) compared with Q1. RCS analysis demonstrated a significant nonlinear association between choline intake and all-cause mortality (P for nonlinearity = 0.025). The overall cancer prevalence association was nonsignificant, except for colon cancer, where each 100 mg increase in choline intake indicated a 23% reduced risk. Conclusion Elevated choline intake demonstrates an inverse association with CVD and colon cancer, while moderate consumption exhibits a correlated reduction in mortality. Additional comprehensive investigations are warranted to elucidate the broader health implications of choline.